ANXIETY, DEPRESSION AND PSYCHOLOGICAL DISTRESS IN PATIENTS WITH OSTEO-ARTHRITIS - Khan, Sabiha; Kalsoom, Ume; Hanifa, Bibi; Begum, Raheela (Journal of Postgraduate Medical Institute, 2017)
Objectives: To explore depression and anxiety among patients with osteoarthritis and to find out the gender differences in these patients. Methodology: The data was collected from private clinics and orthopedic ward of Khyber Teaching Hospital, Peshawar using convenient sampling technique in 2014. The sample comprised of 200 subjects. Among these (n=100) were suffering from osteoarthritis, while contro group (n=100) was also taken from patients visited to OPD with complaints of bodyaches. Men and women equally participated in the study. Results: In the the present research age range of the sample was 30-60 years (mean 47.05, ±8.906). Osteoarthritis sufferers were more anxious and depressed as compared to control group (p value 0.000). Gender differences for study variables were also significant (p value 0.000). Conclusions: Depression, anxiety and psychological distress were high in osteoarthritis patients as compared to control group. Women had more anxiety and depression as compared to men.